MODERNISASI PENDIDIKAN ISLAM DALAM PERSPEKTIF AZYUMARDI AZRA - Aisah, Iis; Husni, H.; Darisman, Dede (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2015)
This research seeks to explore and analyze the concept of modernization of Islamic education according to Azyumardi Azra. The results of this study conclude that: 1) The concept of Islamic education concerns three important things, namely: a) the purpose of education, both general goals which are the purpose of human life, as well as special objectives that are praxis; b) Islamic education curriculum in addition to being oriented towards fostering and developing religious values ​​in students, must now also give special emphasis to the mastery of science and technology; c) democratization of Islamic education aims at the end of the formation of a democratic, clean, moral, and moral Indonesian society and clinging to the value of civilization; 2) Modernization of Islamic education according to Azyumardi Azra relating to: (a) Input from the community into the education system, including ideological-normative; Political mobilization; Economic mobilization; Social mobilization; Culture mobilization; (b) Output for the community. includes changes in the value system; Political output; Economic output; Social output; and cultural output; 3) The relevance of Azra's thinking about the modernization of Islamic education with national education that Islamic religious education is a compulsory curriculum that must be presented in learning.